Economic, social, and cultural capital and ESQ in academic achievement: A comparison of Afghan and Iranian students - Pishghadam, Reza; Naji Meidani, Elham; Momenzadeh, Seyed Mohammad Ebrahim; Hasanzadeh, Saba; Miri, Mir Abdullah (Frontiers in Psychology, 2023)
The present study aimed to investigate the role of different types of capital, including economic, social, and cultural, as well as emo-sensory intelligence (ESI) in the academic achievement of students in the two contexts of Afghanistan and Iran. For this purpose, a total of 317 students from both countries participated in the study. They were asked to fill out the Social and Cultural Capital Questionnaire (SCCQ) and the Emo-sensory Intelligence Questionnaire (ESI-Q). Their grade point average (GPA) was taken as the indicator of their academic achievement. The findings revealed that students’ level of cultural capital and emo-sensory quotient (ESQ) had a significantly positive role in their academic achievement (p<.05). Moreover, significant differences were found between the two contexts in terms of the level of capital, with Afghan students having significantly more cultural capital, and Iranian students having significantly higher economic capital (p<.05). Iranian students were also found to have a significantly higher level of ESQ compared to Afghan students (p<.05). Finally, the results were discussed, and implications and suggestions for further research were provided.